Evaluation of Antimicrobial Efficacy of Different Irrigants Mixed with Silver Nanoparticles – An In Vivo Study - Ajay Chhabra; Himani Mehra; Priyanka Yadav; K. P. Ramya; Saravana B. Prathap; Mallika Sengupta; Sona J. Parvathy; Vandana Chhabra (Journal of Pharmacy and Bioallied Sciences)
Aim: To evaluate the antimicrobial efficacy of different irrigants combined with silver nanoparticles. Materials and Methods: Thirty-five patients were divided into seven groups (two control and five experimental), including Group 1: negative control (normal saline), Group 2: positive control (sodium hypochlorite), and Group 3 (sodium hypochlorite + AgNP), Group 4 (Twin Kleen), Group 5 (Twin Kleen + AgNP), Group 6 (Q Mix), and Group 7 (Q Mix + AgNP). Pre- and post-treatment bacterial samples were collected for analysis. Results: Sodium hypochlorite combined with silver nanoparticles demonstrated the highest antimicrobial efficacy among the tested irrigants, with a significant difference confirmed by the Chi-square statistical analysis. Conclusion: Within the limitations of the study, it can be concluded that sodium hypochlorite when mixed with the silver nanoparticles showed higher antimicrobial efficacy as compared to the other tested groups.